Phosphorus-based flame-retardant functional filler and preparation method thereof
By introducing pyrene groups on the copper polyphosphate skeleton and covering the benzimidazolyl resin on its surface, the problem of the existing phosphorus-nitrogen-based flame retardant not lasting flame retardant under dry conditions is solved, the flame retardant effect and antistatic properties are significantly improved, and the compatibility and dispersion of fillers in the substrate are improved.
Patent Information
- Application Number
- CN202411984730.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing phosphorus-nitrogen-based flame retardant has a short flame retardant effect under dry conditions, and the composite process of flame retardant and antistatic agent is complicated, resulting in poor dispersion of fillers in the substrate, affecting the mechanical properties and service life of the material.
By coating the copper skeleton on the surface of polyammonium phosphate, and using the chemical bonding of 1,3-diaminopyrene and terephthalic acid, pyrene groups are introduced into the copper skeleton to increase the structural strength; at the same time, the benzimidazolyl resin is coated for the second time to enhance the density of the carbonized layer and improve the flame retardant effect.
The flame retardant effect, antistatic properties and moisture resistance of the phosphorus-based flame retardant functional fillers are significantly improved, the compatibility and dispersion of the fillers in the substrate are improved, and the service life of the material is extended.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame retardants, and in particular relates to a phosphorus-based flame retardant functional filler and a preparation method thereof. Background Art
[0002] Phosphorus-based flame retardant materials have high flame retardant efficiency, low smoke release and good environmental protection. They are mainly composed of phosphorus and nitrogen and do not contain halogen. They are a new type of flame retardant material developed on the basis of being used as flame retardant coatings. With the development of social and life needs, polymer materials are widely used due to their mechanical, insulating and chemical resistance properties. For the flammable problem of polymer materials, adding flame retardants is the most direct and effective improvement method.
[0003] In the polymer material products used in the coal mining, petroleum, chemical, rubber, powder processing and other industries, since the polymer material has a very high resistivity, the charge is not easy to conduct away, so it accumulates on the surface to form static electricity. The traditional method is to add a small amount of surfactant or other hydrophilic substances and antistatic agent to the polymer material to obtain the static electricity effect. However, under relatively dry conditions, the surface absorbs limited water, and the surfactant or other hydrophilic substance will slowly migrate to the surface of the material, resulting in the amount of surfactant or other hydrophilic substance in the material becoming less and less. In addition, since flame retardancy and antistatic are two relatively independent processes, compounding flame retardants and antistatic agents is a complicated process, which makes the total filler amount in the substrate very large. The poor compatibility of the two fillers with the substrate makes the filler poorly dispersed in the substrate, which ultimately leads to unstable mechanical properties of the composite material and reduces the service life of the flame retardant.
[0004] Chinese patent application CN102585498B discloses an antistatic and flame retardant phosphorus-nitrogen flame retardant and a preparation method thereof. Ammonium polyphosphate and water form a suspension slurry, aniline or its derivatives are added, and the mixture is stirred continuously to obtain a phosphorus-nitrogen flame retardant having both antistatic and flame retardant functions. However, in this solution, aniline and ammonium polyphosphate cannot be evenly dispersed only by physical stirring, and the flame retardant effect of the flame retardant obtained lacks durability. In addition, polyaniline itself has certain water absorption properties, which further weakens the flame retardant performance of the flame retardant and shortens its service life. Summary of the invention
[0005] The purpose of the present invention is to provide a phosphorus-based flame-retardant functional filler. A layer of copper skeleton is coated on the surface of ammonium polyphosphate by an ion exchange method, and a pyrene group with higher strength is introduced into the copper skeleton structure by chemical bonding of the amino group of 1,3-diaminopyrene and the carboxyl group of terephthalic acid. The ammonium polyphosphate is coated with a benzimidazole-based resin for a second time. The two coating layers can synergistically increase the density of the carbonized layer of the phosphorus-based flame-retardant functional filler when the flame-retardant effect is exerted, thereby improving the flame-retardant effect. The benzimidazole-based resin contains repeated imidazole units, which can significantly improve the flame-retardant effect of the phosphorus-based flame-retardant functional filler, and the imidazole group can be used as a proton carrier to promote proton conductivity and improve the antistatic property of the phosphorus-based flame-retardant functional filler.
[0006] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a phosphorus-based flame retardant functional filler comprises the following steps: Step 1: Add 1,3-diaminopyrene, terephthalic acid, chloroform and deionized water into a reactor, dissolve sodium hexadecyl sulfate as a surfactant in an ethanol solution with a mass fraction of 60-70% and add the solution into the reactor, stir for 1-2 hours at 50-60°C and 400-500r / min, add copper chloride into the reactor, continue stirring and reacting for 3-4 hours, filter, wash the filter cake with deionized water for 2-3 times, and vacuum dry at 60-80°C for 14-16 hours to obtain a metal coating material.
[0007] Step 2: Add the metal coating material, ammonium polyphosphate and 60-70% ethanol solution by mass into the reactor, stir at 50-60°C and 400-500r / min for 30-40min under a nitrogen atmosphere, heat to 80-90°C, continue stirring and reacting for 4-5h, filter, wash the filter cake with deionized water for 2-3 times, and vacuum dry at 60-80°C for 24-26h to obtain a modified flame retardant.
[0008] Step 3: Add 3,3-diaminobenzidine, 4-hydroxybenzoic acid phenyl ester, diphenyl sulfoxide and toluene into a reaction kettle, under nitrogen protection, stir and react at 140-150°C and 500-600r / min for 2.5-3h, heat to 250-260°C, stir and react at 500-600r / min for 1-2h, continue to heat to 280-290°C, stir and react at 500-600r / min for 1-2h, cool naturally, filter, wash the filter cake with acetone and methanol in a water bath, and vacuum dry at 60-80°C to obtain a benzimidazolyl powder.
[0009] Step 4: Add benzimidazole powder, acrylic acid and deionized water into a reactor, stir and react at 60-70°C and 500-600r / min for 40-60min, add styrene into the reactor, introduce nitrogen protection, stir and react at 95-100°C and 500-600r / min for 1-2h, cool to 55-65°C, add sodium sulfite as an initiator and polypropylene glycol as a cross-linking agent into the reactor, heat to 70-80°C, stir at 500-600r / min for 3-4h, filter, wash the filter cake with deionized water for 2-3 times, and vacuum dry at 60-80°C for 1-2h to obtain benzimidazole resin powder.
[0010] Step 5: Add the benzimidazole resin powder and deionized water into the reactor, stir the reaction at 60-70°C and 500-600r / min for 40-60min, add the modified flame retardant into the reactor, stir at 60-70°C and 500-600r / min for 40-60min, filter, wash the filter cake with deionized water for 2-3 times, and vacuum dry at 60-80°C for 1-2h to obtain a composite flame retardant.
[0011] Step six: add ferric chloride hexahydrate, sodium citrate and ethylene glycol into the reaction kettle, stir for 20-30 min at 40-50°C and 500-600r / min, add sodium acetate and composite flame retardant into the reaction kettle, heat to 90-100°C, continue stirring for 4-5h, cool naturally, filter, wash the filter cake with deionized water for 2-3 times, and vacuum dry at 60-80°C for 1-2h to obtain a phosphorus-based flame retardant functional filler.
[0012] Furthermore, in step 1, the dosage ratio of 1,3-diaminopyrene, terephthalic acid, chloroform, deionized water, sodium hexadecyl sulfate, ethanol solution and cupric chloride is 100-120g: 120-150g: 50-60mL: 200-300mL: 10-12g: 100-120mL: 80-90g.
[0013] Furthermore, in step 2, the usage ratio of the metal coating material, ammonium polyphosphate and ethanol solution is 80-90 g: 100-120 g: 200-300 mL.
[0014] Furthermore, in step three, the usage ratio of 3,3-diaminobenzidine, 4-hydroxybenzoic acid phenyl ester, diphenyl sulfoxide and toluene is 200-300 g: 200-250 g: 500-600 mL: 100-150 mL.
[0015] Furthermore, in step 4, the usage ratio of benzimidazole powder, deionized acrylic acid water, styrene, sodium sulfite and polypropylene glycol is 80-90g: 100-110g: 300-400mL: 400-500mL: 15-20g: 10-12mL.
[0016] Furthermore, in step five, the dosage ratio of the benzimidazole-based resin powder, deionized and modified flame retardant is 120-140 g: 300-350 mL: 80-90 g.
[0017] Furthermore, in step six, the dosage ratio of ferric chloride hexahydrate, sodium citrate, ethylene glycol, sodium acetate and composite flame retardant is 100-120g:40-50g:500-600mL:10-15g:80-90g.
[0018] Beneficial effects of the present invention: 1. The phosphorus-based flame-retardant functional filler prepared by the present invention has excellent flame-retardant effect, antistatic property and moisture-proof ability, and has good compatibility when used as a filler in a material; the surface of the modified flame retardant of the present invention is coated with a layer of copper skeleton with high strength and dense structure, and the pyrene group with higher strength is introduced into the copper skeleton structure through chemical bonding of the amino group of 1,3-diaminopyrene and the carboxyl group of terephthalic acid, thereby significantly increasing the structural strength and stability of the copper skeleton; by coating the modified flame retardant with a benzimidazole-based resin for a second time, the second coating layer can cooperate with the first coating layer, and can increase the density of the carbonized layer of the phosphorus-based flame-retardant functional filler when it exerts a flame-retardant effect, thereby further improving the flame-retardant effect.
[0019] 2. The benzimidazole powder has a double-terminal hydroxyl group in its structural formula, one end of which is bonded to acrylic acid, and the other end is combined with the carboxyl group on the surface of the modified flame retardant, so that the benzimidazole resin is evenly and stably wrapped on the surface of the modified flame retardant, and has excellent waterproof performance, which can avoid the decrease in flame retardant effect caused by water absorption of phosphorus-based flame retardant functional fillers; the benzimidazole group in the benzimidazole resin structural formula contains repeated imidazole units, which can act as a proton carrier, promote proton conductivity, and improve the antistatic property of phosphorus-based flame retardant functional fillers.
[0020] 3. The phosphorus-based flame-retardant functional filler prepared by the present invention has nano-ferroferric oxide deposited on its surface. Ferroferric oxide has excellent heat resistance and chemical stability, and can further enhance the flame retardant effect of the flame retardant. Ferroferric oxide has a large hardness, and after being loaded on the surface of the flame retardant, it can improve the wear resistance of the flame retardant and extend its service life. The copper skeleton of the first coating layer and the ferroferric oxide deposited on the surface of the second coating layer have a catalytic effect, and can synergistically play a catalytic role to promote the phosphorylation of ammonium polyphosphate, generate more phosphoric acid substances in the early stage, and is conducive to the formation of an expanded carbon layer. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Embodiment 1: A method for preparing a phosphorus-based flame retardant functional filler, comprising the following steps: S1: 100 g of 1,3-diaminopyrene, 120 g of terephthalic acid, 50 mL of chloroform and 200 mL of deionized water were added to a reactor, 10 g of sodium hexadecyl sulfate as a surfactant was dissolved in 100 mL of 60% ethanol solution and added to the reactor, stirred at 50°C and 400 r / min for 1 h, 80 g of copper chloride was added to the reactor, and the stirring reaction was continued for 3 h. The filter cake was washed twice with deionized water and dried in vacuo at 60°C for 14 h to obtain a metal coating material.
[0023] S2: Add 80g of metal coating material, 100g of ammonium polyphosphate and 200mL of 60% ethanol solution into the reactor, stir at 50℃ and 400r / min for 30min under nitrogen atmosphere, heat to 80℃, continue stirring and react for 4h, filter, wash the filter cake twice with deionized water, and vacuum dry at 60℃ for 24h to obtain the modified flame retardant.
[0024] The amino group of 1,3-diaminopyrene and the carboxyl group of terephthalic acid are chemically bonded, and under the action of surfactants, a copper skeleton with high strength and strong rigidity is generated. The remaining amino groups on the metal coating material are ion-exchanged with the ammonium groups of ammonium polyphosphate through an ion exchange method, so that the metal coating material is evenly coated on the surface of the ammonium polyphosphate, which can effectively increase the density of the carbonized layer when the phosphorus-based flame retardant functional filler plays a flame retardant role, thereby improving the flame retardant effect.
[0025] S3: Add 200 g of 3,3-diaminobenzidine, 200 g of phenyl 4-hydroxybenzoate, 500 mL of diphenyl sulfoxide and 100 mL of toluene into a reactor, and under nitrogen protection, stir and react at 140°C and 500 r / min for 2.5 h, heat to 250°C, stir and react at 500 r / min for 1 h, continue to heat to 280°C, stir and react at 500 r / min for 1 h, cool naturally, filter, wash the filter cake with acetone and methanol in a water bath, and dry in vacuo at 60°C to obtain a benzimidazolyl powder.
[0026] S4: Add 80g of benzimidazole powder, 100g of acrylic acid and 300mL of deionized water into a reactor, stir and react at 60°C and 500r / min for 40min, add 400mL of styrene into the reactor, introduce nitrogen protection, stir and react at 95°C and 500r / min for 1h, cool to 55°C, add 15g of sodium sulfite as an initiator and 10mL of polypropylene glycol as a cross-linking agent into the reactor, heat to 70°C, stir at 500r / min for 3h, filter, wash the filter cake twice with deionized water, and vacuum dry at 60°C for 1h to obtain benzimidazole resin powder.
[0027] The benzimidazole powder has a double-terminal hydroxyl group in its structural formula, one of which is bonded to acrylic acid. It is polymerized with styrene under the action of an initiator and a crosslinking agent to form a benzimidazole resin. When the acrylic acid monomer loses its carboxyl group, its hydrophilicity will be greatly reduced. When copolymerized with an excess of styrene, the water absorption performance of the obtained resin is greatly weakened. The imidazole repeating unit of the benzimidazole group can significantly improve the flame retardant effect of the phosphorus-based flame retardant functional filler, and the imidazole group can serve as a proton carrier to promote proton conductivity and improve the antistatic property of the phosphorus-based flame retardant functional filler.
[0028] S5: Add 120 g of benzimidazole resin powder and 300 mL of deionized water into a reactor, stir and react at 60°C and 500 r / min for 40 min, add 80 g of modified flame retardant into the reactor, stir at 60°C and 500 r / min for 40 min, filter, wash the filter cake twice with deionized water, and vacuum dry at 60°C for 1 h to obtain a composite flame retardant.
[0029] S6: Add 120g of ferric chloride hexahydrate, 50g of sodium citrate and 600mL of ethylene glycol into a reactor, stir at 40°C and 500r / min for 20min, add 15g of sodium acetate and 90g of a composite flame retardant into the reactor, heat to 90°C, continue stirring for 4h, cool naturally, filter, wash the filter cake twice with deionized water, and vacuum dry at 60°C for 1h to obtain a phosphorus-based flame retardant functional filler.
[0030] The benzimidazole resin is coated on the surface of the modified flame retardant. The hydroxyl group at the other end of the benzimidazole structure is combined with the carboxyl group on the surface of the modified flame retardant, so that the benzimidazole resin can be evenly and stably coated on the surface, and nano-ferroferric oxide is deposited on the surface. Ferroferric oxide has excellent heat resistance and chemical stability, which can further enhance the flame retardant effect of the flame retardant. Ferroferric oxide has a large hardness. After being loaded on the surface of the flame retardant, it can improve the wear resistance of the flame retardant and extend its service life. It can also promote the phosphorylation of ammonium polyphosphate, generate more phosphate substances at an early stage, and is beneficial to the formation of an expanded carbon layer.
[0031] Embodiment 2: A method for preparing a phosphorus-based flame retardant functional filler, comprising the following steps: S1: 110 g of 1,3-diaminopyrene, 130 g of terephthalic acid, 55 mL of chloroform and 250 mL of deionized water were added to a reactor, 11 g of sodium hexadecyl sulfate as a surfactant was dissolved in 110 mL of 65% ethanol solution and added to the reactor, stirred at 55°C and 450 r / min for 1.5 h, 85 g of copper chloride was added to the reactor, and the stirring reaction was continued for 3.5 h. The mixture was filtered, and the filter cake was washed twice with deionized water. The mixture was vacuum dried at 70°C for 15 h to obtain a metal coating material.
[0032] S2: Add 85g of metal coating material, 110g of ammonium polyphosphate and 250mL of 65% ethanol solution into the reactor, stir at 55℃ and 450r / min for 35min under nitrogen atmosphere, heat to 85℃, continue stirring and react for 4.5h, filter, wash the filter cake twice with deionized water, and vacuum dry at 70℃ for 25h to obtain the modified flame retardant.
[0033] S3: Add 250g of 3,3-diaminobenzidine, 230g of phenyl 4-hydroxybenzoate, 550mL of diphenyl sulfoxide and 120mL of toluene into a reactor, and under nitrogen protection, stir and react at 145°C and 550r / min for 2.7h, heat to 255°C, stir and react at 550r / min for 1.5h, continue to heat to 285°C, stir and react at 550r / min for 1.5h, cool naturally, filter, wash the filter cake with acetone and methanol in a water bath, and dry in vacuo at 70°C to obtain a benzimidazolyl powder.
[0034] S4: Add 85g of benzimidazole powder, 105g of acrylic acid and 350mL of deionized water into a reactor, stir and react at 65°C and 550r / min for 50min, add 450mL of styrene into the reactor, introduce nitrogen protection, stir and react at 98°C and 550r / min for 1.5h, cool to 60°C, add 18g of sodium sulfite as an initiator and 11mL of polypropylene glycol as a cross-linking agent into the reactor, heat to 75°C, stir at 550r / min for 3.5h, filter, wash the filter cake twice with deionized water, and vacuum dry at 70°C for 1.5h to obtain benzimidazole resin powder.
[0035] S5: Add 130g of benzimidazole resin powder and 330mL of deionized water into a reactor, stir and react at 65°C and 550r / min for 50min, add 85g of modified flame retardant into the reactor, stir at 65°C and 550r / min for 50min, filter, wash the filter cake with deionized water for 3 times, and vacuum dry at 70°C for 1.5h to obtain a composite flame retardant.
[0036] S6: Add 110g of ferric chloride hexahydrate, 45g of sodium citrate and 550mL of ethylene glycol into a reactor, stir at 45°C and 550r / min for 25min, add 13g of sodium acetate and 85g of a composite flame retardant into the reactor, heat to 95°C, continue stirring for 4.5h, cool naturally, filter, wash the filter cake with deionized water for 3 times, and vacuum dry at 70°C for 1.5h to obtain a phosphorus-based flame retardant functional filler.
[0037] Embodiment 3: A method for preparing a phosphorus-based flame retardant functional filler, comprising the following steps: S1: 120 g of 1,3-diaminopyrene, 150 g of terephthalic acid, 60 mL of chloroform and 300 mL of deionized water were added to a reactor, 12 g of sodium hexadecyl sulfate as a surfactant was dissolved in 120 mL of 70% ethanol solution and added to the reactor, stirred at 60°C and 500 r / min for 2 h, 90 g of copper chloride was added to the reactor, the reaction was continued with stirring for 4 h, filtered, the filter cake was washed with deionized water 3 times, and vacuum dried at 80°C for 16 h to obtain a metal coating material.
[0038] S2: Add 90g of metal coating material, 120g of ammonium polyphosphate and 300mL of 70% ethanol solution into the reactor, stir at 60℃ and 500r / min for 40min under nitrogen atmosphere, heat to 90℃, continue stirring and react for 5h, filter, wash the filter cake with deionized water 3 times, and vacuum dry at 80℃ for 26h to obtain the modified flame retardant.
[0039] S3: 300 g of 3,3-diaminobenzidine, 250 g of phenyl 4-hydroxybenzoate, 600 mL of diphenyl sulfoxide and 150 mL of toluene were added into a reactor. Under nitrogen protection, the mixture was stirred at 150°C and 600 r / min for 3 h. The mixture was heated to 260°C and stirred at 600 r / min for 2 h. The mixture was further heated to 290°C and stirred at 600 r / min for 2 h. The mixture was naturally cooled and filtered. The filter cake was washed with acetone and methanol in a water bath and dried in a vacuum at 80°C to obtain a benzimidazolyl powder.
[0040] S4: 90 g of benzimidazole powder, 110 g of acrylic acid and 400 mL of deionized water were added to a reactor, and the reaction was stirred at 70°C and 600 r / min for 60 min. 500 mL of styrene was added to the reactor, and nitrogen was introduced for protection. The reaction was stirred at 100°C and 600 r / min for 2 h. The reactor was cooled to 65°C, and 20 g of sodium sulfite as an initiator and 12 mL of polypropylene glycol as a cross-linking agent were added to the reactor. The reactor was heated to 80°C, stirred at 600 r / min for 4 h, filtered, and the filter cake was washed with deionized water 3 times, and vacuum dried at 80°C for 2 h to obtain a benzimidazole resin powder.
[0041] S5: Add 140g of benzimidazole resin powder and 350mL of deionized water into a reactor, stir and react at 70°C and 600r / min for 60min, add 90g of modified flame retardant into the reactor, stir at 70°C and 600r / min for 60min, filter, wash the filter cake with deionized water for 3 times, and vacuum dry at 80°C for 2h to obtain a composite flame retardant.
[0042] S6: Add 120g of ferric chloride hexahydrate, 50g of sodium citrate and 600mL of ethylene glycol into a reactor, stir at 50°C and 600r / min for 30min, add 15g of sodium acetate and 90g of a composite flame retardant into the reactor, heat to 100°C, continue stirring for 5h, cool naturally, filter, wash the filter cake with deionized water for 3 times, and vacuum dry at 80°C for 2h to obtain a phosphorus-based flame retardant functional filler.
[0043] Comparative Example 1: Based on Example 3, the modified flame retardant in step S5 is replaced by ammonium polyphosphate in step S2, and the other steps remain unchanged to prepare a phosphorus-based flame retardant functional filler.
[0044] Comparative Example 2: Based on Example 3, 1,3-diaminopyrene in step S1 is discarded, and the other steps remain unchanged to prepare a phosphorus-based flame retardant functional filler.
[0045] Comparative Example 3: Based on Example 3, the composite flame retardant in step S6 is replaced by the modified flame retardant in step S2, and the other steps remain unchanged to prepare a phosphorus-based flame retardant functional filler.
[0046] Comparative Example 4: Based on Example 3, the composite flame retardant in step S5 is directly used as a phosphorus-based flame retardant functional filler.
[0047] In the embodiments and comparative examples: 1,3-Diaminopyrene, terephthalic acid, chloroform, deionized water, sodium hexadecyl sulfate, ethanol solution, cupric chloride, ammonium polyphosphate, 3,3-diaminobenzidine, phenyl 4-hydroxybenzoate, diphenyl sulfoxide, toluene, ferric chloride hexahydrate, and polypropylene glycol were purchased from Sigma-Aldrich.
[0048] A phosphorus-based flame retardant functional filler prepared in Examples 1 to 3 and Comparative Examples 1 to 4 was filled into ethylene-vinyl acetate copolymer (EVA) for performance testing, and a blank group was set up, in which no phosphorus-based flame retardant functional filler was added; 1 kg of EVA was dried in a vacuum oven at 60°C for 12 hours, the temperature of the front and rear rollers of the mixing mill was raised to 100°C, the front and rear roller distance was adjusted to the minimum, the EVA was plasticized between the front and rear rollers, and then the rollers were wrapped, the roller distance was increased, 80 g of carbon nanotubes as a conductive agent and 50 g of phosphorus-based flame retardant functional filler were added, and the mixing was continued for 10 minutes, and hot pressed at 150°C through a flat vulcanizer, and naturally cooled to obtain an EVA composite material sample.
[0049] 1. Limiting oxygen index: The size of the cut sample is 1260×65×30mm 3 , referring to the limiting oxygen index (LOI) data of EVA composite materials tested according to the standard GB / T2406-2009, to evaluate the flame retardant effect of different samples after adding phosphorus-based flame retardant functional fillers.
[0050] 2 Surface resistivity: Referring to the ASTM D257 standard, the surface resistivity of the EVA composite material sample was measured to evaluate the antistatic ability of the EVA composite material sample after adding phosphorus-based flame retardant functional fillers.
[0051] 3. Impact strength: Referring to the ISO2932003 standard, the EVA composite material samples were subjected to unnotched impact test at room temperature. Each group of samples was tested 5 times and the average value and error value were taken to evaluate the influence of adding phosphorus-based flame retardant functional fillers on the impact strength of EVA composite material samples.
[0052] 4. Tensile strength: Referring to the standard of GB / T528-2009, EVA composite materials samples were tested at room temperature at a tensile speed of 50 mm / min. Each group of samples was tested 5 times and the average value and error value were taken to evaluate the influence of adding phosphorus-based flame retardant functional fillers on the tensile strength of EVA composite materials samples.
[0053] 5. Water contact angle: The measuring instrument is SZ-CAMB3 measuring instrument of Shanghai Xuanzhun Instrument Co., Ltd., and the EVA composite material sample is pressed into a sheet under a pressure of 10MPa using an infrared sheet pressing mold. The average value is taken after three tests at different positions to evaluate the waterproof ability of the EVA composite material sample after adding phosphorus flame retardant functional fillers. The results are shown in Table 1: Table 1 EVA composite material performance test results
[0054] It can be seen from Table 1 that when the phosphorus-based flame retardant functional filler prepared in Examples 1 to 3 of the present invention is used as an EVA filler, the flame retardant effect, impact strength, tensile strength and waterproof ability are significantly better than the comparative example, and the comparative example is better than the blank group in these properties. This result shows that the phosphorus-based flame retardant functional filler prepared by the present invention has excellent flame retardant properties, good antistatic properties and outstanding waterproof properties. When filled into EVA, the filler does not have an adverse effect on the impact strength and tensile strength of the material, which fully proves that it has good compatibility with EVA.
[0055] In Comparative Example 1, the modified flame retardant in step S5 is replaced by ammonium polyphosphate in step S2, and the benzimidazole-based resin is directly coated on the surface of the ammonium polyphosphate to obtain a phosphorus-based flame retardant functional filler. The lack of the first layer of the copper skeleton coating is not conducive to the formation of a dense carbonized layer during the flame retardant process, resulting in a decrease in the limiting oxygen index. The copper skeleton coating can not only enhance the structural strength of the overall material, but also improve its impact strength and tensile strength. Therefore, its absence will lead to a decrease in these two mechanical properties. In addition, the copper skeleton and the second coating are tightly connected by chemical bonds, which can effectively promote the second coating to stably perform its antistatic and moisture-proof functions.
[0056] In Comparative Example 2, 1,3-diaminopyrene in step S1 is discarded, and the resulting copper skeleton coating layer exhibits general structural strength, which is not conducive to the formation of a tight and dense carbonized layer during the flame retardant process, thereby resulting in a decrease in the limiting oxygen index, impact strength and tensile strength. This structural defect further affects the antistatic and moisture-proof properties of the material. It is worth noting that compared with Comparative Example 1, only the pyrene component is missing from the current copper skeleton structure, which makes its overall performance slightly better than that of Comparative Example 1.
[0057] In Comparative Example 3, the composite flame retardant in step S6 is replaced by the modified flame retardant in step S2, and the second coating layer is lost, resulting in a decrease in the strength and density of the carbonized layer formed during the flame retardant process, resulting in a decrease in the limiting oxygen index, impact strength and tensile strength; the second coating layer is a resin containing benzimidazole groups, and the imidazole groups can serve as proton carriers to promote proton conductivity and improve the antistatic properties of phosphorus-based flame retardant functional fillers. After the loss, the charge is not easily conducted away and is easily accumulated on the surface, thereby increasing the surface resistivity; the benzimidazole-based resin is prepared by the polymerization reaction of benzimidazole groups with acrylic acid and styrene, and exhibits excellent waterproof properties. When this performance is reduced, its water contact angle will decrease significantly. However, even so, its performance is still better than that of the untreated blank control group. This phenomenon reveals that the steric hindrance effect of the first coating layer has a certain influence on the water absorption performance of the material.
[0058] In Comparative Example 4, the composite flame retardant in step S5 is directly used as a phosphorus-based flame retardant functional filler, resulting in the lack of catalytically active nano-ferroferric oxide deposition on the surface of the second coating layer. The ferroferric oxide itself has a certain flame retardancy and can cooperate with the copper skeleton in the first coating layer to jointly catalyze the phosphorylation process of ammonium polyphosphate and promote the formation of the expanded carbon layer. When the surface of the second coating layer lacks this nano-ferroferric oxide, the limiting oxygen index, impact strength and tensile strength of the material will all decrease.
[0059] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0060] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a phosphorus-based flame retardant functional filler, characterized in that: The steps include: Step 1: Add the metal coating material, ammonium polyphosphate and 60-70wt% ethanol solution into a reactor, stir at 50-60°C and 400-500r / min for 30-40min under a nitrogen atmosphere, heat to 80-90°C, continue stirring for 4-5h, filter, wash the filter cake with deionized water 2-3 times, and vacuum dry to obtain a modified flame retardant; Step 2: Add the benzimidazole resin powder and deionized water into a reactor, stir at 60-70°C and 500-600r / min for 40-60min, add the modified flame retardant into the reactor, continue stirring for 40-60min, filter, wash the filter cake with deionized water for 2-3 times, and vacuum dry to obtain a composite flame retardant; Step 3: Add ferric chloride hexahydrate, sodium citrate and ethylene glycol into the reactor, stir at 40-50°C and 500-600r / min for 20-30min, add sodium acetate and the composite flame retardant into the reactor, heat to 90-100°C, continue stirring for 4-5h, cool naturally, filter, wash the filter cake with deionized water 2-3 times, and vacuum dry to obtain a phosphorus-based flame retardant functional filler.
2. The method for preparing a phosphorus-based flame retardant functional filler according to claim 1, characterized in that: The usage ratio of the metal coating material, ammonium polyphosphate and ethanol solution in step 1 is 80-90g: 100-120g: 200-300mL.
3. The method for preparing a phosphorus-based flame retardant functional filler according to claim 1, characterized in that: The usage ratio of the benzimidazole-based resin powder, deionized and modified flame retardant in step 2 is 120-140 g: 300-350 mL: 80-90 g.
4. The method for preparing a phosphorus-based flame retardant functional filler according to claim 1, characterized in that: The dosage ratio of ferric chloride hexahydrate, sodium citrate, ethylene glycol, sodium acetate and composite flame retardant in step three is 100-120g: 40-50g: 500-600mL: 10-15g: 80-90g.
5. The method for preparing a phosphorus-based flame retardant functional filler according to claim 1, characterized in that: The metal cladding material is prepared by the following steps: 1,3-diaminopyrene, terephthalic acid, chloroform and deionized water are added to a reaction kettle, sodium hexadecyl sulfate is dissolved in a 60-70wt% ethanol solution and then added to the reaction kettle, stirred at 50-60°C and 400-500r / min for 1-2h, copper chloride is added to the reaction kettle, stirring and reacting is continued for 3-4h, suction filtering is performed, the filter cake is washed with deionized water for 2-3 times, and vacuum drying is performed to obtain a metal coating material; The dosage ratio of the 1,3-diaminopyrene, terephthalic acid, chloroform, deionized water, sodium hexadecyl sulfate, ethanol solution and copper chloride is 100-120g: 120-150g: 50-60mL: 200-300mL: 10-12g: 100-120mL: 80-90g.
6. The method for preparing a phosphorus-based flame retardant functional filler according to claim 1, characterized in that: The benzimidazole resin powder in step 2 is prepared by the following steps: Add benzimidazole powder, acrylic acid and deionized water into a reactor, stir at 60-70°C and 500-600 r / min for 40-60 min, add styrene into the reactor, introduce nitrogen protection, stir at 95-100°C and 500-600 r / min for 1-2 h, cool to 55-65°C, add sodium sulfite and polypropylene glycol into the reactor, heat to 70-80°C, stir at 500-600 r / min for 3-4 h, filter, wash the filter cake with ionized water for 2-3 times, and vacuum dry to obtain benzimidazole resin powder.
7. The method for preparing a phosphorus-based flame retardant functional filler according to claim 6, characterized in that: The usage ratio of the benzimidazole-based powder, acrylic acid deionized water, styrene, sodium sulfite and polypropylene glycol is 80-90g: 100-110g: 300-400mL: 400-500mL: 15-20g: 10-12mL.
8. The method for preparing a phosphorus-based flame retardant functional filler according to claim 6, characterized in that: The benzimidazole-based powder is prepared by the following steps: Add 3,3-diaminobenzidine, 4-hydroxybenzoic acid phenyl ester, diphenyl sulfoxide and toluene into a reaction kettle, stir at 140-150°C and 500-600r / min for 2.5-3h under nitrogen protection, heat to 250-260°C, stir at 500-600r / min for 1-2h, heat to 280-290°C, stir at 500-600r / min for 1-2h, cool naturally, filter, wash the filter cake by heating in a water bath with acetone and methanol, and dry in vacuo to obtain a benzimidazolyl powder.
9. The method for preparing a phosphorus-based flame retardant functional filler according to claim 8, characterized in that: The usage ratio of the 3,3-diaminobenzidine, 4-hydroxybenzoic acid phenyl ester, diphenyl sulfoxide and toluene is 200-300 g: 200-250 g: 500-600 mL: 100-150 mL.
10. A phosphorus-based flame retardant functional filler, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Antistatic and anti-flaming phosphorous nitrogen series flame retardant and preparation method thereof
CN102585498B
Method for preparing water-soluble ferroferric oxide nano particle
CN103274478A
Cited By
Preparation and application of PNS / POSS-NH2 coating material
CN121172381A